Analisis Perbandingan Harga Pokok Produksi Produk Makanan pada UMKM Ahyusni Aqiqah & Catering Menggunakan Metode Full Costing, Variable Costing, dan Job Order Costing. - Dinda Cahyaning Aulia; Ujang Suherman; Thomas Nadeak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The objective of this study is to analyze the differences in the results of Cost of Goods Sold (COGS) calculations using the full costing, variable costing, and job order costing methods, as well as to determine the most efficient method for improving the effectiveness of production cost management. The research method used is a descriptive comparative quantitative study, with the subject being the SME Ahyusni Aqiqah & Catering for the period 2023–2025. Data were collected through observation, interviews, and documentation, then analyzed using the three methods and the results were compared. The research findings indicate that the full costing method yields a higher and relatively stable COGS because it includes all production costs. The variable costing method yields the lowest COGS because it includes only variable costs. Meanwhile, the job order costing method shows fluctuating results due to periods without production, which cause fixed costs to accumulate and be charged to the following period. The conclusion of this study is that the choice of COGS calculation method significantly affects the cost per portion, so it must be aligned with managerial objectives and business characteristics. Consequently, the Job Order Costing method is more suitable for order-based SMEs, full costing is better suited for long-term pricing, and variable costing is appropriate for short-term cost control.